Harnessing WYE-132 as an inhibitor of the mTOR signaling enriches the cytotoxicity effect of vinblastine in B16F10 melanoma cancer cells. (December 2020) - Khaki-Khatibi, Fatemeh; Zeinali, Mahdi; Ramezani, Bahman; Sabzichi, Mehdi; Mohammadian, Jamal; Hamishehkar, Hamed
Graphical abstract: Highlights: Melanoma is a possibly lethal skin malignancy. WYE-132 is specific inhibitor of mTORC1 and mTORC2 signaling pathways. in vitro studies showed significant down-regulation in anti-apoptotic genes. WYE-132 and vinblastine presented synergistic anticancer effects. Abstract: This study aimed to evaluate the synergistic anticancer effect of vinblastine and WYE-132, a specific inhibitor of the mammalian target of rapamycin (mTOR), on B16F10 melanoma cancer cells. MTT assay, Annexin V, and DAPI staining along with Real-Time PCR were conducted to understand the mechanistic roles of mTOR pathway in melanoma cancer cells. The IC50 values for vinblastine and WYE-132 were 39.4 ± 1.8 nM and 145.2 ± 4.5 nM, respectively. The co-administration of WYE-132 and vinblastine in B16F10 cells offered a significant increase in the growth inhibitory effect of vinblastine along with a two-fold escalation in the percentage of apoptotic cells. The calculation of gene expression levels confirmed a visible fall in anti-apoptotic Bcl-2, Ki-67 and Mcl-1 accompanied by a surge in pro-apoptotic Bax mRNA levels ( p < 0.05). Thus, we showed that the combination of WYE-132 and vinblastine could be a promising approach for dealing with patients with melanoma cancers.